2002
DOI: 10.1152/japplphysiol.00002.2002
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I, IgA, and IgG responses to bovine colostrum supplementation during training

Abstract: This study examined the effect of bovine colostrum (Dynamic colostrum) supplementation on blood and saliva variables (study 1) and the absorption of orally administered human recombinant insulin-like growth factor (IGF)-I (rhIGF-I) labeled with 123I (123I-rhIGF-I) (study 2). In study 1, adult male and female athletes were randomly assigned in a double-blind fashion to either an experimental (Dynamic; n = 19) or a control (Placebo; n = 11) group. The former consumed daily 20 g of Dynamic supplement, and the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
7

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(96 citation statements)
references
References 37 publications
3
86
7
Order By: Relevance
“…However, it was seen that there were no differences in IgA between the experimental and control groups (Table 1). Similar results (10,14,15) were obtained from some sports branches. But (7) the average values of serum IgA were estimated to be higher than the values mentioned in this research.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, it was seen that there were no differences in IgA between the experimental and control groups (Table 1). Similar results (10,14,15) were obtained from some sports branches. But (7) the average values of serum IgA were estimated to be higher than the values mentioned in this research.…”
Section: Discussionsupporting
confidence: 86%
“…And it was seen that there was no difference in the serum IgG between the experimental and control groups (Table 1). Researches showed that the colostrum supplement had no effect on IgG levels in athletes (14), sportsmen (7,15) and swimmers (10). They informed that the serum IgG levels were between 6.5-16.0 g/L in adult persons (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in calves, rats and piglets, oral ingestion of IGF-I has been shown to provoke various local effects on gastrointestinal tract [1,2,9,10,124,237,241], and to increase blood IGF-I concentration [8,236]. In human athletes, Mero et al [133] also showed that orally administered IGF-I increased blood IGF-I concentration but the peptide was fragmented (96%) when in circulation. Those results thus suggest that dietary IGF-I may be absorbed and cause local and systemic effects.…”
Section: Insulin-like Growth Factormentioning
confidence: 99%
“…1 In recent years, researchers have attempted to identify nutritional countermeasures to exercise-induced changes in IgA concentration in saliva. Effect of different kind of supplementation both on exercise induced decreases in salivary IgA and incidence of URTI , was investigated, such as glutamine [13,14], carbohydrate [9], protein [14], nucleotide [21], vitamin C [25], and bovine colostrum supplementation [5,22].…”
Section: Effect Of Sensory Stimulation On Salivary Iga Secretion Ratementioning
confidence: 99%